Ecology, Democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Ryan, J. Michael (COVID-19: Volume I: Global Pandemic, Societal Responses, Ideological Solutions, 2020)
The SARS-CoV-2 virus, and the associated COVID-19 pandemic, is perhaps the greatest threat to life, and lifestyles, the world has known in more than a century. The scholarship included here provides critical insights into the ethics and ideologies, inequalities, and changed social understandings that lie at the heart of this pandemic. This volume maps out the ways in which the pandemic has impacted (most often disproportionately) societies, the successes and failures of means used to combat the virus, and the considerations and future possibilities – both positive and negative – that lie ahead. While the pandemic has brought humanity together in some noteworthy ways, it has also laid bare many of the systemic inequalities that lie at the foundation of our global society. This volume is a significant step toward better understanding these impacts. The work presented here represents a remarkable diversity and quality of impassioned scholarship and is a timely and critical advance in knowledge related to the pandemic. This volume and its companion, COVID-19: Volume II: Social Consequences and Cultural Adaptations, are the result of the collaboration of more than 50 of the leading social scientists from across five continents. The breadth and depth of the scholarship is matched only by the intellectual and global scope of the contributors themselves. The insights presented here have much to offer not just to an understanding of the ongoing world of COVID-19, but also to helping us (re-) build, and better shape, the world beyond.
Keywords: COVID-19; disease & health Issues; health

How to conceptualize an alternative to platform capitalism according to the re-embedding process of K. Polanyi ? [Comment penser l'alternative au capitalisme de plateforme dans une logique de réencastrement polanyien ?] - Aufrère, Laura; Eynaud, Philippe; Maurel, Lionel; Vercher-Chaptal, Corinne (CEPN Working Papers, 2020)
The article considers alternatives to platform capitalism in a logic of Polanyian re-embedding. Stemming from case studies in the car-pooling, delivery and hosting sectors, the results uncover hybrid business models in which the market principle is used in the service of reciprocal logic. Rejecting the formal algorithmic rationality of capitalist platforms, the alternatives seek to align individual and collective behavior with values of solidarity and goals of general interest. They are experimenting with original methods of scaling up, based on the federation of communities, respectful of their anchoring in the substantive economy. The results make it possible to think of complementarities between different forms of embedding likely to be played out on several scales, and open perspectives for rethinking public policies vis-à-vis the experiments of the solidarity economy and the commons.
Keywords: coopérativisme de plateforme; decommodification; digital platforms; démar- chandisation; plateformes numériques; platform cooperativism; re-embedding; reciprocity; ré-encastrement; réciprocité; substantive economy; économie substantive

Introduction : exploring markets - Peck, Jamie; Berndt, Christian; Rantisi, Norma (Market/Place: Exploring Spaces of Exchange, 2020)
The origin of the present volume was an invitational workshop focused on questions of the spatiality and diversity of markets, held at the Karl Polanyi Institute of Political Economy in Montreal in the summer of 2017. This was an apt meeting place in a more than literal sense. Although many of those in attendance did not subscribe explicitly to a Polanyian worldview or mode of analysis, most had engaged with Polanyi’s work in different ways. Some had made extensive contributions to neo-Polanyian scholarship, while others were more closely affiliated to radical political economy, performativity approaches or poststructuralism. In this context, more pertinent were a series of broadly aligned sympathies with what might be characterized as Polanyian dispositions, including: shared recognition of the importance of respectful, constructive and non-dogmatic exchange across an interdisciplinary range of heterodox and critical positions; overlapping concerns with the potential of empirically engaged and “substantivist” investigation (to borrow the Polanyian terminology), not just in testing and tweaking extant theories but in the construction of new insights, understandings and socio-political visions; and mutual commitments to humane, emancipatory and sustainable modes of socio-economic and ecological development.
Keywords: Karl Polanyi Institute of Political Economy; economic geography; markets